STEM-based approach: A learning design to improve critical thinking skills - Pratiwi, Anggi Nurul; Aisyah, Nyimas; Somakim, Somakim; Kamran, Muhammad (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: The STEM approach in learning integrates the concepts of science, the use of technology, engineering, and mathematics, which support enthusiastic, creative, and active learning activities by students. In this context, it is necessary to develop ways to improve the understanding of the concept of a three-variable system of linear equations in high school students.Aim: The purpose of this study was to produce a learning trajectory in the three-variable linear equation system material using the STEM approach for high school students, with the main objective of increasing students' critical thinking skills.Method: The method used is 'design research', which includes three stages: preliminary, teaching experiment, and retrospective analysis. The research was conducted at a public high school in Palembang City, using qualitative descriptive data analysis techniques based on observation, interviews, and tests designed to measure students' critical thinking skills.Result: The results of this study are STEM-based learning trajectories that are effective in helping students understand the system of three-variable linear equations. The hypothetical learning trajectory (HLT) that has been implemented is a successful tool in helping students understand the concept and can improve students' critical thinking skills.Conclusion: The STEM-based mathematics learning design produced in this study has the potential to serve as a reference for teachers in improving students' critical thinking skills, especially in the subject matter of a system of three-variable linear equations. It is hoped that this approach will become a valuable tool in helping students understand mathematical concepts in greater depth in the future.